Comparison of the Ultrasound Visibility of Tissue Markers in Metastatic Lymph Nodes after Neoadjuvant Chemotherapy in Patients with Breast Cancer - Ka Eun Kim; Eun Young Ko; Boo-Kyung Han; Eun Sook Ko; Ji Soo Choi; Haejung Kim; Jeong Eon Lee; Hyunwoo Lee (Diagnostics, 2022)
This study aimed to investigate the differences in ultrasound (US) visibility for the localization of clipped metastatic lymph nodes after neoadjuvant chemotherapy (NAC), according to tissue marker type. This single-center retrospective study included 59 consecutive patients with breast cancer who underwent tissue marker insertion for histologically proven metastatic axillary lymph nodes before NAC, between March 2020 and August 2021. Two breast tissue markers were used: UltraClip™ (n = 29) and UltraCor™ Twirl™ (n = 30). The US visibility of tissue markers after NAC and the successful excision rate of the clipped lymph nodes were compared between the two types of tissue markers. UltraCor™ Twirl™ showed better overall US visibility than UltraClip™ after NAC (86.7% vs. 72.4%), but the difference was statistically insignificant. In the absence of residual metastatic lymph nodes on US after NAC (n = 32), UltraCor™ Twirl™ showed significantly better US visibility (83.3%, 15/18) than UltraClip™ (42.9%, 6/14; p = 0.027). The marker type was not associated with the successful excision of the clipped lymph node. UltraCor™ Twirl™ showed better US visibility than UltraClip™ in the metastatic axillary lymph nodes after NAC in the absence of residual suspicious lymph nodes on US.